Indonesian Education Policy and Management in Resolving Social Disaster - Desratri Timur Tresnanti; Anwar Kurniadi; Deffi Ayu Puspito; Pujo Widodo; Kusuma, Kusuma (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Indonesia, an archipelagic nation rich in natural resources, religious variety, and ethnic diversity, faces social complexities due to these diversities. Social disputes often arise from racial, religious, and social justice disparities, as well as resource competition. This research employs a descriptive qualitative approach to explore how education can prevent and resolve conflicts by promoting diversity, tolerance, and peace. By analyzing community dynamics through literature studies and theories such as the Explanatory Theory and Peace Education Theory, the study aims to provide new insights into educational management techniques and policies for conflict prevention and resolution. Findings indicate that politics, religion, and ethnicity often lead to social strife in Indonesia. Peace education, through inclusive curricula and teacher training, is recommended as an effective solution. Effective educational management requires community involvement, continual assessment, cross-sector cooperation, and adaptability to regional challenges. Thus, education is posited as a primary tool for fostering a just and peaceful society in Indonesia.